클로버씨스트선충 방제용 녹비작물 선발을 위한 잡초 자원 탐색 - 김진원(Jin-Won Kim); 고형래(Hyoung-Rai Ko) (Weed & turfgrass science, 2023)
최근 강원도 배추 재배지에서 씨스트선충의 발생면적이 크게 증하고 있기 때문에 확산 방지 및 피해 저감을 위한 종합적 방제연구가 요구되고 있다. 이의 일환으로 생물훈증효과가 있는 것으로 알려진 국내 자생 십자화과 잡초 중 갯무(Raphanus sativus var.hortensis f.raphanistroides)와들갓(Sinapis arvensis)의활용가능성을확인하기위해본연구를수행하였다. 갯무와 들갓의 종자를 각각 제주와 대구, 울산, 해남에서 종자를 채집하여 파종심도 및 유황비료에 따른 출아율의차이를 비교하였고, 클로버씨스트선충(Heterodera trifolii)의 증식률을 조사하였다. 그 결과, 토양심도 1-4 cm까지 출아율의 유의적인 차이는 없었으며, 안정적인 출아율을 보였다. 유황비료 0~100 kg ha-1처리에 따른 출아율의 감소도 없었기때문에, 잡초자원의 선충방제효과를 극대화하기 위해 유황비료를 사용할 수 있을 것으로 판단된다. 모든 잡초자원의사탕무씨스트선충 증식률은 56~345%였기 때문에 저항성으로 판정할 수 없었다. 그러나 제주 갯무 및 울산 들갓은 씨스트선충의증식률이상대적으로낮아활용할수있는가능성이 있을것으로 판단되었다. Recently, cyst nematodes have been problematic in Kimchi-cabbage field and development of integrated nematode management method has been required to prevent yield reduction. This study was conducted to examine applicability of Brassicaceae weed species for green manure with nematicidal effect. A wild radish (Raphanus sativus var. hortensis f. raphanistroides) from Jeju and three wild mustard (Sinapis arvensis) from Daegu, Ulsan, and Haenam were used for comparison of emergence rate by burial depth and sulfur fertilizer application. As a result, the emergence rate was stable at over 1 cm burial depth and not different among the treatment except 0 cm. There was no significant difference in sulfur application at 0, 50, 100 kg ha-1 suggesting that sulfur fertilizer would be applicable to maximize bio-fumigation effect. Although all the weed species were not resistant to clover cyst nematode (Heterodera trifolii) showing 56~345% female index, R. sativus var. hortensis f. raphanistroides from Jeju and S. arvensis from Ulsan could be utilizable for green-manure crop resulting from relatively low female index. KCI Citation Count: 0